Eight-Year Delay in Unilateral Traumatic Cataract Diagnosis Leading to Deprivation Amblyopia and Small-Angle Sensory Esotropia - Najiyyah, Siti Ulfatun; Sari, Padmi Kartika; Andari, Marie Yuni (Universitas Airlangga, 2026)
Introduction: Traumatic cataract in children is often unnoticed, especially in unilateral cases. Severe vision loss in one eye leads the brain to suppress input from the weaker eye. If the condition is treated after the visual development period is complete, visual function may not fully recover even after the underlying cause is removed; this is known as amblyopia. Loss of binocular fusion weakens ocular alignment, causing esotropia. Case Presentation: A 13-year-old girl reported blurred vision in her right eye after accidentally closing her left eye. She had no prior ocular history. Her mother recalled that at age five the patient fell from a slide, causing swelling around the right eye that was untreated. Examination revealed a mature cataract in the right eye with 8.75Δ esotropia and visual acuity of 1/60. Cataract surgery was successfully performed. The ocular segments were within normal limits, and funduscopy after pupil dilation showed no optic disc or retinal abnormalities. However, the visual acuity remained uncorrected, at 1/60. Following the diagnosis of amblyopia and esotropia, the patient was advised to perform six-hour daily patching. Eighteen months postoperatively, a home visit revealed persistent 8.75Δ esotropia, with right eye visual acuity remaining 1/60, while the intraocular lens and ocular segments remained normal. According to her mother, the patient was inconsistent with patching therapy. Conclusions: This case emphasizes that delayed diagnosis and treatment of traumatic cataracts in children during the critical period may result in amblyopia and strabismus that are difficult to treat despite successful cataract surgery.